Una riflessione sugli ultimi sviluppi degli studi mitologici Razmišlenija o razvitii mifologičeskih issledovanij v poslednee vremja - Mikhailov, Nikolai (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The author analyses the progress of mythological research methods in the last few years. From the theoretical point of view it is important to distinguish between the general, archetypal discussion of mythological on the one hand, and between the concrete researches on the other. From the practical point of view, the value of the concrete studies, which refer to the mythological material, is important. The article deals with two books of general mythological value: Z. Šmitek, Kristalna gora, Ljubljana 1998 and M. Yevzlin, El jardín de los monstruos, Biblioteca Nueva, Madrid 1999.